Sex Differences in Immunity: Implications for the Development of Novel Vaccines Against Emerging Pathogens - Fathi, Anahita; Addo, Marylyn M.; Dahlke, Christine (Frontiers in Immunology, 2021)
Vaccines are one of the greatest public health achievements and have saved millions of lives. They represent a key countermeasure to limit epidemics caused by emerging infectious diseases. The Ebola virus disease crisis in West Africa dramatically revealed the need for a rapid and strategic development of vaccines to effectively control outbreaks. Seven years later, in light of the SARS-CoV-2 pandemic, this need has never been as urgent as it is today. Vaccine development and implementation of clinical trials have been greatly accelerated, but still lack strategic design and evaluation. Responses to vaccination can vary widely across individuals based on factors like age, microbiome, co-morbidities and sex. The latter aspect has received more and more attention in recent years and a growing body of data provide evidence that sex-specific effects may lead to different outcomes of vaccine safety and efficacy. As these differences might have a significant impact on the resulting optimal vaccine regimen, sex-based differences should already be considered and investigated in pre-clinical and clinical trials. In this Review, we will highlight the clinical observations of sex-specific differences in response to vaccination, delineate sex differences in immune mechanisms, and will discuss the possible resulting implications for development of vaccine candidates against emerging infections. As multiple vaccine candidates against COVID-19 that target the same antigen are tested, vaccine development may undergo a decisive change, since we now have the opportunity to better understand mechanisms that influence vaccine-induced reactogenicity and effectiveness of different vaccines.